Potential Protective Effects of Bioactive Constituents from Chinese Propolis against Acute Oxidative Stress Induced by Hydrogen Peroxide in Cardiac H9c2 Cells. (27th February 2017) - Sun, Liping; Wang, Kai; Xu, Xiang; Ge, Miaomiao; Chen, Yifan; Hu, Fuliang
Abstract : Chinese propolis (CP) is known as a health food but its beneficial effects in protecting cardiomyocytes remain elusive. Here, we investigated the effects of CP and its active compounds on hydrogen peroxide (H2 O2 ) induced rats cardiomyocytes (H9c2) oxidative injury. Cell viability decreases induced by H2 O2 were mitigated by different CP extracts using various solvents. From these active fractions, six active compounds were separated and identified. Among tested isolated compound, the cytoprotective activities of three caffeates, caffeic acid phenethyl ester (CAPE), benzyl caffeate (BZC), and cinnamyl caffeate (CNC), exerted stronger effects than chrysin, pinobanksin, and 3, 4-dimethoxycinnamic acid (DMCA). These three caffeates also increased H9c2 cellular antioxidant potential, decreased intracellular calcium ion (C a 2 + i ) level, and prevented cell apoptosis. Overall, the cardiovascular protective effects of the CP might be attributed to its caffeates constituents (CAPE, BZC, and CNC) and provide evidence for its usage in complementary and alternative medicine.